Technical and Operational Analysis of Marine Airbag-Assisted Ship Docking - Puspa Ningrum, Ainun Chandra; Yusril Syam, Muh; Maulidah, Hikmah; Wahidah, Jusma; Jeremy Verian Sitorus, Chris (Indonesian Journal of Maritime Technology, 2025)
Ship docking operations require careful planning and precise implementation to ensure safety and operational efficiency. One widely applied method in shipyard practice is the use of marine airbags to support vessels during docking and undocking processes. This study analyzes the application of a marine airbag-assisted docking system for the barge BG. Liana at PT. Jhonlin Marine Trans using an analytical and field-based approach. The analysis focuses on determining the required number of airbags, evaluating load distribution, and identifying factors contributing to airbag failure during docking operations. Vessel principal dimensions and marine airbag specifications were used as primary input parameters, while field observations were conducted to assess actual operational conditions. The results indicate that a minimum of 21 marine airbags is required to ensure adequate load sharing and structural safety; however, only seven airbags were deployed in practice, leading to excessive load concentration and increased risk of airbag failure. The failure analysis demonstrates that the observed damage was predominantly caused by controllable operational factors, including inadequate airbag quantity, improper placement, pressure inconsistencies, and runway conditions. These findings highlight the importance of strict compliance with analytical planning and operational procedures to enhance safety and reliability in marine airbag-assisted docking operations.